Let's solve the equation step by step for Part A.
Part A: Solve the equation \( 5 + x - 14 = x - 7 \)
-
Simplify the left side: \[ 5 + x - 14 = x - 7 \] Combine \(5\) and \(-14\): \[ -9 + x = x - 7 \]
-
Eliminate \(x\) from both sides: Subtract \(x\) from both sides: \[ -9 = -7 \]
-
Analyze the result: The equation \(-9 = -7\) is a false statement, indicating that there are no values for \(x\) that satisfy this equation.
Therefore, there is no solution to the equation \(5 + x - 14 = x - 7\).
Final answer for Part A: No solution.
Part B: Verify the solution using the values \(2\), \(0\), and \(3\)
Since we concluded in Part A that there is no solution, we can substitute the values of \(2\), \(0\), and \(3\) into the original equation to confirm that they indeed do not satisfy the equation.
-
Substituting \(x = 2\): \[ 5 + 2 - 14 = 2 - 7 \] Calculate the left side: \[ 5 + 2 - 14 = -7 \] Calculate the right side: \[ 2 - 7 = -5 \] Since \(-7 \neq -5\), \(x = 2\) does not satisfy the equation.
-
Substituting \(x = 0\): \[ 5 + 0 - 14 = 0 - 7 \] Calculate the left side: \[ 5 - 14 = -9 \] Calculate the right side: \[ 0 - 7 = -7 \] Since \(-9 \neq -7\), \(x = 0\) does not satisfy the equation.
-
Substituting \(x = 3\): \[ 5 + 3 - 14 = 3 - 7 \] Calculate the left side: \[ 5 + 3 - 14 = -6 \] Calculate the right side: \[ 3 - 7 = -4 \] Since \(-6 \neq -4\), \(x = 3\) does not satisfy the equation.
Final answer for Part B: All the tested values (\(2\), \(0\), and \(3\)) do not satisfy the equation \(5 + x - 14 = x - 7\), confirming that there is no solution.